The Meaning and Function of the Fishermen's Mantra of the Ternate Community, North Maluku - Rasid, Amarfan; Sumarwati, Sumarwati; Anindyarini, Atikah (International journal of multicultural and multireligious understanding, 2025)
Fishermen’s incantations in Ternate constitute an integral part of the local community’s cultural and spiritual life, which are still preserved today as an oral tradition. These incantations are not only believed to possess magical powers that protect and assist fishermen in obtaining marine resources, but also reflect a harmonious relationship between humans and nature, particularly the sea. However, as they continue to exist primarily as an oral tradition, Ternate fishermen’s incantations are at risk of disappearing if not studied and documented. This study aims to identify the meanings and functions of fishermen’s incantations as a reflection of the local wisdom of the Ternate community. A qualitative method with an ethnographic approach was employed. The data sources consisted of fishermen or fishing groups who possess such incantations, as well as local cultural experts. The sampling techniques used were purposive sampling and snowball sampling. Data were collected through interviews and focus group discussions (FGD). To ensure data validity, source triangulation and theoretical triangulation were applied. Data were analyzed using an interactive model. The findings reveal that the meanings and functions of Ternate fishermen’s incantations reflect the local wisdom of coastal communities, encompassing both literal and symbolic meanings. At the heuristic level, the incantations consist of simple prayers for safety, protection, and abundant catches, whereas at the hermeneutic level they embody cosmological symbols that position the sea as a sacred entity and a space of dialogue between humans, nature, and God. Their functions include social aspects as a means of strengthening fishermen’s solidarity, cultural aspects as a medium for transmitting maritime identity, and religious aspects that emphasize the value of monotheism through Islamic prayers. Thus, the incantations are not merely spiritual tools, but also value systems that preserve tradition, identity, and the cosmic balance of the Ternate fishing community.